Penerapan Wavelet Daubechies pada Teknik Estimasi Gerak Bilateral - Istri Iswari, A.A. Made Agung; Widyantara, I Made Oka; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro; Vol 21 No 1 (2022): (Januari - Juni) Majalah Ilmiah Teknologi Elektro, 2022)
DVC has the characteristics of lighter encoder performance by transferring the efficiency of the field of motion to the decoder. The characteristics of DVC are similar to FRUC which is a technique to improve the quality of video display from the decoder side by inserting interpolated frames. In this study, multi-resolution bilateral motion estimation based on pyramid wavelets is proposed by comparing the order of wavelets contained in the daubechies wavelet. The parameters compared in this study are PSNR and the computational complexity of the proposed method to improve the quality of the video reconstruction from the decoder side. This study shows that the use of the daubechies wavelet order in the proposed method can obtain sufficient category of PSNR values of db6 with a value of 27.37 dB for video images with moving background characteristics and moving objects, good categories of db7 and db10 with a value of 34.8 dB and 32.06 dB for video images with fixed background characteristics and moving objects, and video images with moving background characteristics and fixed objects. The selection of the wavelet order on the daubechies wavelet can be adjusted to the characteristics of the video image that will be used.